Biological maturity and injury in elite youth football - Le Gall, F.; Carling, C.; Reilly, T. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The purpose of the present study was to investigate injury according to biological maturity in elite under-14 youth football players based at the National Football Institute, France. Over 10 seasons, injury incidence, severity and distribution were compared in 233 players classed according to individual biological maturity determined by skeletal age into three cohorts as early, normal and late maturers.